2019
DOI: 10.1002/cne.24806
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping morphological and functional properties between M4 and M5 intrinsically photosensitive retinal ganglion cells

Abstract: Multiple retinal ganglion cell (RGC) types in the mouse retina mediate pattern vision by responding to specific features of the visual scene. The M4 and M5 melanopsinexpressing, intrinsically photosensitive retinal ganglion cell (ipRGC) subtypes are two RGC types that are thought to play major roles in pattern vision. The M4 ipRGCs overlap in population with ON-alpha RGCs, while M5 ipRGCs were recently reported to exhibit opponent responses to different wavelengths of light (color opponency).Despite their seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 49 publications
6
64
1
Order By: Relevance
“…M4 ipRGCs have been characterized as having the largest dendritic arbor area and soma diameter among all known ipRGCs (Estevez et al, 2012) and a recent study identified them intersectionally in Opn4 Cre : Z/EG mice using coincidental GFP and SMI32 signals (Sonoda et al, 2019). In 37 AP‐stained retinas, we analyzed 15 these M4‐like Tbr2 + RGCs with large dendritic arbors and somata (arbor diameter: 327.95 ± 48.51 μm; soma diameter: 19.28 ± 3.49 μm; N = 15) and relatively loose dendritic arbors (Figure 7(a,b′)).…”
Section: Resultsmentioning
confidence: 99%
“…M4 ipRGCs have been characterized as having the largest dendritic arbor area and soma diameter among all known ipRGCs (Estevez et al, 2012) and a recent study identified them intersectionally in Opn4 Cre : Z/EG mice using coincidental GFP and SMI32 signals (Sonoda et al, 2019). In 37 AP‐stained retinas, we analyzed 15 these M4‐like Tbr2 + RGCs with large dendritic arbors and somata (arbor diameter: 327.95 ± 48.51 μm; soma diameter: 19.28 ± 3.49 μm; N = 15) and relatively loose dendritic arbors (Figure 7(a,b′)).…”
Section: Resultsmentioning
confidence: 99%
“…If S5-Gbx2 ACs are the CRH-1 subtype, as hypothesized above, we would expect that they provide inhibition onto “sustained” suppressed-by-contrast (SbC) RGCs and On aRGCs (also known as the M4 subtype of intrinsically photosensitive RGCs [ipRGCs]) ( Estevez et al, 2012 ; Jacoby and Schwartz, 2018 ; Jacoby et al, 2015 ; Park et al, 2018 ). Sublamina 5 also contains the dendrites of the M2, M3, and M5 subtypes of ipRGCs, which are involved in visual modalities involved in light avoidance, pupillary reflex, and circadian rhythm behaviors ( Schmidt et al, 2011 ; Sonoda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…5E3). Cells studied based on these properties and subsequently visualized by confocal microscopy exhibited morphological properties characteristic of M5 ipRGCs: monostratified dendritic arbors within the inner margin of the IPL, dense dendritic branching, and relatively small dendritic and somatic diameters (Stabio et al, 2018;Sonoda et al, 2020) (see Fig. 4D1).…”
Section: Methodsmentioning
confidence: 99%